We steal secrets [videorecording (DVD)] : the story of Wikileaks - Gibney, Alex (Universal Studios Home Entertainment, 2013)
A gripping, edge-of-your-seat thriller, about Julian Assange and the creation of Wikileaks, the controversial website that facilitated the largest security breach in the U.S. history. Paralleling Assange's rise and fall with that of Pfc. Bradley Manning, the troubled young soldier who leaked hundreds of thousands of classified documents, and multi-layered expose about transparency in the information age and our ever-elusive search for the truth.